Incision and Drainage With Primary Fistulotomy of Perianal Abscess Is Safe and Effective in Neonates: A Long-Term Follow-Up Study - Yin, Wanbin; Li, Laian; Su, Lin; Wang, Shuai (Frontiers in Pediatrics, 2022)
Objective: Perianal abscess (PA) in neonates is poorly understood, and its management remains controversial. The aim of this study was to compare incision and drainage (ID) with or without primary fistulotomy in the management of neonatal first-time perianal abscess. Methods: A retrospective comparative study was conducted for neonates with first-time PA treated with incision and drainage with primary fistulotomy (IDF) versus ID between 2008 and 2017. Results: 138 patients (137 boys and 1 girl) were identified; 65 in the IDF group and 73 in the ID group. The median follow-up was 6.5 years (range 4-13 years). Baseline characteristics were similar between the 2 groups. Cure rate in the IDF group (98.5%, 64/65) was significantly higher than that in the ID group (80.8%, 59/73; P=0.001). The rate of fistula formation in the IDF group (1.5%, 1/65) was significantly lower than that in the ID group (13.7%, 10/73; P=0.01). The rate of abscess recurrence was not statistically different (P=0.12), despite the fact that the IDF group (0%, 0/65) seemed to have a better outcome than the ID group (5.5%, 4/73). No fecal incontinence was observed in any of our patients. Conclusions: First-time PA in neonates can be treated safely and effectively by IDF or by ID alone. The former may be advantageous over the latter in terms of the rate of cure and fistula formation.